Közép-Európa: élboly vagy periféria? : a versenyképesség és a társadalmi fejlődés alakulása a rendszerváltás után - Csath, Magdolna (Közép-Európai Közlemények, 2013)
This paper investigates how the original objectives of the system change have been achieved in Central-Eastern Europe. It concentrates on examining not only the economic, but also the social achievements in the region by comparing competitiveness rankings and social indicators in six countries: Austria, Czech Republic, Poland, Slovenia, Slovakia and Hungary. Finland is picked as a benchmark, best practice country in the field of economic development and competitiveness. Special attention is paid to analysing how quality of life, human development and human satisfaction have changed during the selected time horizon in the surveyed countries. Corruption, as a performance-damaging factor is also taken into account. The competitiveness analysis is based on the IMD and the World Economic Forum rankings. The paper concludes by presenting a deteriorating competitiveness and social situation in Hungary, and an improving performance in Poland. Based on the research findings the paper suggests a stronger focus on developing human resources, social capital and other soft factors instead of concentrating solely on creating growth measured by GDP. This would help to close not only the economic, but also the social development gap between the core and the Central-Eastern European countries.